دراسة أثر متغيري (عدد السياح- الليالي السياحية) على الدخل القومي في سورية - برهوم, أديب; سليطين, فاطر; إبراهيم, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى دراسة بعض المتغيرات السياحية في سورية كعدد القادمين العرب، عدد القادمين الأجانب، عدد الليالي السياحية التي قضاها الأجانب، عدد الليالي السياحية التي قضاها العرب، وإبراز دور كل مؤشر من هذه المؤشرات على الدخل القومي. ونعمل على تحديد أهم العراقيل التي تعترض تنمية وتعزيز السياحة والنهوض بقطاع السياحة ليقوم بدوره الاقتصادي والاجتماعي على أكمل وجه، وتقديم بعض الاقتراحات التي تؤدي إلى تطوير هذا القطاع ومساهمته في الدخل القومي. This research aims to study some of the variables as the number of tourist arrivals in Syria, the Arabs, the number of foreign arrivals, the number of nights spent by foreigners, the number of nights spent by the Arabs, and the study aims to highlight the role of each of these indicators on the national income. We are working to identify the main obstacles to development and promotion of tourism and the promotion of the tourism sector to play its role in the economic and social roles to the fullest, and to make some suggestions that lead to the development of this sector and its contribution to the national income.